Altered neocortical tactile but preserved auditory early change detection responses in Friedreich ataxia. Issue 8 (August 2019) - Naeije, Gilles; Wens, Vincent; Bourguignon, Mathieu; Goldman, Serge; Pandolfo, Massimo; De Tiège, Xavier
Highlights: MEG has a higher sensitivity than SSEPs in Friedreich ataxia (FRDA). Neuromagnetic responses at SI cortex are delayed and reduced in amplitude in FRDA. Tactile mismatch responses at secondary somatosensory cortex are altered in FRDA. Abstract: Objective: To study using magnetoencephalography (MEG) the spatio-temporal dynamics of neocortical responses involved in sensory processing and early change detection in Friedreich ataxia (FRDA). Methods: Tactile (TERs) and auditory (AERs) evoked responses, and early neocortical change detection responses indexed by the mismatch negativity (MMN) were recorded using tactile and auditory oddballs in sixteen FRDA patients and matched healthy subjects. Correlations between the maximal amplitude of each response, genotype and clinical parameters were investigated. Results: Evoked responses were detectable in all FRDA patients but one. In patients, TERs were delayed and reduced in amplitude, while AERs were only delayed. Only tactile MMN responses at the contralateral secondary somatosensory cortex were altered in FRDA patients. Maximal amplitudes of TERs, AERs and tactile MMN correlated with genotype, but did not correlate with clinical parameters. Conclusions: In FRDA, the amplitude of tactile MMN responses at SII cortex are reduced and correlate with the genotype, while auditory MMN responses are not altered. Significance: Somatosensory pathways and tactile early change detection are selectively impaired in FRDA.